Psychological capital and breakthrough innovation: The role of tacit knowledge sharing and task interdependence - Hu, Rui; Li, Yingchao; Huang, Jiayu; Zhang, Ying; Jiang, Rong; Dunlop, Elizabeth (Frontiers in Psychology, 2023)
Compared with incremental innovation, breakthrough innovation is essential to sustaining competitive advantage, but breakthrough innovation has the characteristics of high standards and strict requirements. As the main body and foundation of enterprises, the attitude and behavior of employees play a vital role in enterprise innovation. Based on the positive organizational behavior theory and knowledge management theory, the purpose of this paper is to investigate the relationship between psychological capital and breakthrough innovation, and we also integrate tacit knowledge sharing and task interdependence into the research framework, so as to further explore the influence mechanism of employees’ psychological capital on breakthrough innovation. Although Yunnan coffee industry has developed rapidly in recent years its competitiveness is still relatively weak, however, innovation has the potential to break the bottleneck of development in this industry. Utilizing a quantitative method, this study takes employees of Yunnan coffee enterprises as investigation objects, the data was analyzed using regression analysis through SPSS 24.0, and the existence of mediation was further verified by Bootstrap test. The results showed that the psychological capital of employees have a positive impact on breakthrough innovation; tacit knowledge sharing partially mediates the relationship between psychological capital and breakthrough innovation; and task interdependence plays a moderating role, that is, the stronger the task interdependence, the stronger the influence of employee psychological capital on breakthrough innovation. This study enriches the research on the influencing factors of breakthrough innovation of Yunnan coffee industry, expands the application scenarios of the related theory, emphasizes that the importance of psychological capital and the breakthrough innovation is the result of the interaction and value-added linkage of various internal and external resources.